A service quality Description of the quality of service for officers at the Sangurara Health Center, Tatanga District, Palu City - Imelda Kantohe; Fitri Arni Rasyidi; Parmi Parmi; Ni Kadek Armini; Sri Purwiningsih; Meilin Anggreyni (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2023)
Service quality is a central point for the Sangurara Health Center where there are aspects that have not been fulfilled, from the tangibles aspect in the form of facilities, the reliability aspect in the form of accurate service, the assurance aspect in the form of growing trust, the empathy aspect in the form of sincere concern. Some patients who visited the Sangurara Health Center stated that the quality of the existing services was not satisfactory because patients were still waiting a long time to receive services. The purpose of this research is to know the description of the service quality of officers at the Sangurara Health Center, Tatanga District, Palu City. This type of research is a descriptive research with a quantitative approach. The variables studied are tangibles, reliability, responsiveness, assurance, empathy. The population is outpatients at the Sangurara Health Center. Sample 44 respondents. The analysis used is univariate analysis. The results of this study show that the service quality of officers in terms of tangibles is 100% good, from reliability most are not good 56.8% and good are 43.2%, responsiveness is mostly good 90.9% and those that are not good are 9.1%, assurance is partially 59.1% is not good and 40.9% is good, and empathy is mostly good 79.5% and 20.5% is not good. It is concluded that the service quality of officers in terms of tangibles as a whole respondents considered good, from reliability most considered not good enough, responsiveness mostly thinks it's good, assurance mostly thinks it's not good, empathy mostly thinks it's good. Keywords: Quality, Service, Staff, Health Center